Reorientational Motions and Ionic Conductivity in (NH4)2B10H10 and (NH4)2B12H12 - Gradišek, A.; Krnel, M.; Paskevicius, Mark; Hansen, B.; Jensen, T.; Dolinsek, J. (American Chemical Society, 2018)
We investigated molecular dynamics in two ammonium borane systems from the group of promising ion conductors. The investigation was performed by means of 1H and 11B NMR spectroscopy and spin-lattice relaxation techniques. We identified two reorientational processes, the rotations of NH4 units that are present already at low temperatures, and rotations of large boron cages, B10H10 or B12H12, which are thermally activated and become prominent above 250 K. Activation energies for these processes were determined. In addition, solid-state ion conductivity measurements were conducted to determine poor NH4 conductivity of both systems.